Assessing the climate change impact on floodplain inundation map in the Chiang Mai municipality, upper Ping river basin of Thailand - K. Boonrawd; C. Jothityangkoon (Lowland Technology International, 2018)
Coupling of water balance model and floodplain inundation model is developed to receive projected rainfall time series from two types of regional climate model (RCM). Providing Regional Climates for Impacts Studies (PRECIS) and Meteorological Research Institute (MRI) are RCM with resolution 0.2 x 0.2 degree (grid sie 20 x 20 km) daily time step, from year 20152044. They are generated from ECHAM 4 climate models. Empirical quantile mapping is used for bias correction of projection rainfall that its adjustment factors are estimated from comparison between observed and past projection rainfall from base-time period, year 1985-2014. A floodplain inundation model is applied based on 1D rating curve approach. This model receives peak runoffs as results from the water balance model, and generate flood extent in flood plain and draw flood inundation map of Chiang Mai municipality with different return periods. These expected results show the increase of flood inundation extent as a consequence of climate change